Two Sequential Authentication Method on Locker Security System Using Open-Sourced Smartphone - Dodon Yendri (JITCE (Journal of Information Technology and Computer Engineering), 2019)
Lockers are commonly used to store luggages temporarly. For security purposes, lockers are equipped with conventional lock keys to keep it safe. In order to enhance the security aspects, there are several options by optimalizing current emerging technology that is two-factors authentication. This method is commencing by inputting some PIN (Personal Identification Numbers) code then it would trigger confirmation access by smartphone to unlock the lockers. By having this security schemes, any unauthorized users could not allowed any attempt to unseal the locker. More over, the owner could immediately recognize if there was any suspicious access. The result of this research shows that the system could unlock the locker by inputting the correct PIN and verified access by achieving the successful percentage of 100%. The averages response time is around 6.647 seconds, while any attempt to unlock the locker by inputting the incorrect access gain 100% percentages